Validation of molecular markers for multiple disease resistance in tomato (Solanum lycopersicum) - HUSSAIN, ZAKIR; LATA, SUMAN; MANGAL, MANISHA; TOMAR, B S; YADAV, R K; GOSAVI, GOKUL; KUMAR, ASHWANI; YADAV, PAWAN; MONIKA, MONIKA; YADAV, S K (The Indian Journal of Agricultural Sciences, 2019)
Marker assisted breeding has been successfully used for selecting disease resistance by identifying genetic markers linked to resistance genes/allele. In tomato, availability of molecular markers linked to genes conferring resilience against Tomato leaf curl virus (ToLCV) reaction, late blight, Tomato Mosaic Virus (ToMV) and Tomato gray leaf spot were utilised to develop pyramided MAS derived lines for multiple disease resistance. For this purpose, markers for the tomato leaf curl disease (ToLCD) resistance gene loci Ty-2, Ty-3 and Ty-3a, late blight resistant loci Ph-3, ToMV resistant allele Tm22 and Tomato gray leaf spot resistant gene Sm were validated using PCR assay. The assay correctly predicted the genotypes of tomato breeding lines harbouring resistant as well as susceptible alleles at each loci. Duplexing PCR assay combining two SCAR markers (T0302 and P6-25) for detecting simultaneously 3 important resistance gene loci (Ty-2, Ty-3 and Ty-3a) in tomato genotypes and thereby improving the cost efficiency of the PCR assay. Further, we have validated the Tomato leaf curl New Delhi virus (ToLCNDV) infection in tomato leaves by Reverse transcription (RT) PCR with ToLCNDV genome specific AC4 primers.